Strategies For Writing Local Cuisine Promotional Videos: A Case Study Of Rumah Makan Pindang Kurnia Palembang - Dewi Elisabeth Siregar; Mutia Nasution; Nian Masna Evawati; Koryati Koryati; Aulia Akbar; M.Ghaza Tri Putra (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Culinary tourism plays a vital role in the contemporary tourism industry by showcasing cultural identity through local cuisine. This study develops a bilingual video script (Indonesian–English) to promote Rumah Makan Pindang Kurnia in Palembang, a restaurant famous for authentic pindang dishes. The aim was to design an informative and persuasive promotional tool that enhances visibility of traditional food and supports the preservation of Palembang’s culinary heritage. The research applied a qualitative Research and Development (R&D) model adapted from Plomp (1997). Data collection, conducted from May to August 2025, involved literature review, observation, and interviews with the restaurant owner. The study followed several stages: initial investigation, script design, draft writing, expert validation, revision, and finalization. Validation was carried out by specialists in Indonesian and English scriptwriting, focusing on narrative clarity, linguistic accuracy, and promotional impact. The final product is a bilingual script structured according to Jakacaping’s rhetorical framework—hook, introduction, body, and closing. The script emphasizes the uniqueness of Pindang Kurnia’s recipes, its family legacy, the Ogan Komering Ulu flavor, and dining experiences enriched with traditional vegetables and sambal. Expert feedback confirmed that persuasive language and storytelling strategies effectively increased the script’s appeal for digital promotion. In conclusion, this research demonstrates the potential of bilingual promotional scripts to strengthen digital marketing of local cuisine. By integrating rhetorical strategies, cultural values, and social media platforms, culinary businesses can expand their reach and attract broader audiences. The findings provide practical insights for culinary tourism development and contribute to the promotion of Indonesian culinary heritage.